Evidences of Monomer, Dimer and Trimer of Recombinant Human Cyclophilin A - Zhang, Xin-Chao; Wang, Wei-Dong; Wang, Jin-Song; Pan, Ji-Cheng; Zou, Guo-Lin (Protein and Peptide Letters, 2011)
Cyclophilin A (CyPA) is a cytosolic receptor of immunosuppressive drug cyclosporin A (CsA) which possesses peptidyl-prodyl cis/trans isomerase (PPIase) activity. The recombinant human CyPA (rhCyPA) gene has been expressed in E. coli M15. Purification was performed using salting-out, as well as Sephacryl S-100 and DEAE-Sepharose CL-6B column chromatography. The molecular weight is about 18 kDa, confirmed by SDS-PAGE and mass spectrum. The results of Native-PAGE and immunoblotting showed the existence of three bands, which agreed well with the gel filtration results. The molecular mass of the three bands determined via CTAB gel electrophoresis and SDS-PAGE (rhCyPA cross-linked with glutaraldehyde) was 18 kDa, 36 kDa and 54 kDa respectively. Further more, the native rhCyPA and the cross-linked rhCyPA had the similar chromatographic behavior in gel filtration. All of the evidences above suggest that rhCyPA exists in forms of monomer, dimer and trimer. Moreover, we observed that even at low protein concentrations CyPA largely occurs as a dimer in solution, and enzyme kinetic parameters showed that activity of dimer was much higher than monomer or trimer, which probably have some biological significances.
Keywords: rhCyPA